Dimension Study of Occupational Stress Among College Teachers in Dakshin Dinajpur District, West Bengal (Global Journal of Human-Social Science, 2024)
The present study was conducted with the main objectives to know the occupational stress of college teachers with respect to certain variable like type of college (General Degree college & B.Ed. college). The data were collected by selecting randomly 138 teachers in Dakshin Dinajpur district from general degree college and B.Ed college by using Teacher's Occupational Stress Scale by M. Aftab and T. Khatoon (2013). The sample consisted of 50.72 % teachers from general degree college and 49.28% teachers from B.Ed. colleges. Descriptive statistics like mean, SD were computed and Graphical presentation like Bar diagram and NPC curve shown to represent the data of this study and to carry out this quantitative research work. Normalization of data has been done by using Histogram with normal probability curve. The hypothesis was tested at 0.05 level of significance. Results shows that significance differences of occupational stress of teachers exists between General degree college and B.Ed. college (t=2.31, p=0.022). These finding will be helpful to improve the quality of teaching learning in training colleges.
Keywords: occupational stress; teacher; educator